Traumatic Patellar Tendon Rupture Repair Using Synthetic Ligament Augmentation - Core, Maxime; Anract, Philippe; Raffin, Juliette; Biau, David Jean (The Journal of Knee Surgery, 2020)
Rupture of the patellar tendon is an infrequent pathology, and surgical repair with nonabsorbable sutures is the gold standard for management. Many surgeons augment the repair using one of many proposed methods: cerclage wires, Dall–Miles cables, autologous hamstring grafts, and tendon allografts. In this study, we propose the augmentation of patellar tendon repair using an artificial ligament. The questions to be assessed in this study are as follows: (1) measurement of functional results 1 year after surgery using the Lysholm score and (2) the incidence of both rerupture, and surgical complications within the first year postsurgery, the median knee range of motion at 3 months and 1-year postsurgery, patient satisfaction, and postsurgery patellar height, measured using the Caton–Deschamps Index. In our center, we performed 30 suture repairs of traumatic patellar tendon ruptures between 2015 and 2016. Tendon repair was always augmented using an artificial ligament (LT60, Orthomed). The results were evaluated 1 year after surgery. The 1-year postsurgery median Lysholm score was 96 (first quartile–third quartile [Q1–Q3]: 95–100). None of the following complications were reported: second surgery for any reason, new rupture, and superficial or deep infection. Radiological analysis showed a median Caton Index of 1 (Q1–Q3: 0.9–1) postsurgery. Excellent Lysholm scores were observed 1 year after synthetic ligament augmentation of patellar tendon sutures, with a low rate of complications compared with published studies.
Keywords: synthetic ligament augmentation; patellar tendon; rupture repair